2020
DOI: 10.13057/biodiv/d210833
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: The fruit plant species diversity in the home gardens and their contribution to the livelihood of communities in rural area

Abstract: Abstract. Elfrida, Mubarak A, Suwardi AB. 2020. Short Communication: The fruit plant species diversity in the home gardens and their contribution to the livelihood of rural communities in Tenggulun Sub-district, Aceh Tamiang, Indonesia. Biodiversitas 21: 3670-3675. Home gardens have a significant potential to improve food security and offer a contribution to household income for communities in rural areas. The aim of this study was to assess the diversity of fruit plant species in the home gardens and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
1
22
0
4
Order By: Relevance
“…However, only about 20-22% of them are cultivated, while the rest 78% are still harvested from the wild (Azmin et al 2019). Local communities have long used various plant species for medicinal purposes (Jadid et al 2020;Suwardi et al 2021) as well as for food (Elfrida et al 2020;Navia et al 2015;Navia et al 2020a;Suwardi et al 2020a;Suwardi et al 2020b;Navia et al 2021), traditional ceremonies (Sutrisno et al 2020), and household income (Suwardi et al 2020c). The interaction between humans and plants has long been described as one of the factors influencing human civilization, particularly in medical fields (Yeung et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, only about 20-22% of them are cultivated, while the rest 78% are still harvested from the wild (Azmin et al 2019). Local communities have long used various plant species for medicinal purposes (Jadid et al 2020;Suwardi et al 2021) as well as for food (Elfrida et al 2020;Navia et al 2015;Navia et al 2020a;Suwardi et al 2020a;Suwardi et al 2020b;Navia et al 2021), traditional ceremonies (Sutrisno et al 2020), and household income (Suwardi et al 2020c). The interaction between humans and plants has long been described as one of the factors influencing human civilization, particularly in medical fields (Yeung et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Over a long history, local communities in the Aceh Tamiang District, along with almost 80% of whom live in rural areas, have accumulated a wealth of folk medicinal knowledge and represented many experiences in treating common local diseases. Although the use of medicinal plants in Indonesia has been studied in different locations, particularly in Aceh province (Elfrida et al 2020;Sutrisno et al 2020;Suwardi et al 2020;, it was discovered that many of them were poorly described and neglected. In addition, traditional medicinal knowledge is threatened by a lack of written records and conservative inheritance behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the fruit plant species in the yard or home garden showed that Indonesia has great potential. Previous studies in Aceh Tamiang District reported 39 species of fruit plants (Elfrida et al 2020); in South Aceh District there were 56 species of native edible fruit plants (Suwardi et al 2020), while in Karo District there were 30 species of fruit plant (Silalahi and Nisyawati 2018). This species of native fruit plant plays an important role in the daily life of people living in developing countries, including in cultural events (Mabaya et al 2014;Khruomo and Deb 2018;Sutraningsih 2019;Purwanto 2020).…”
Section: Introductionmentioning
confidence: 96%